Conditional cash transfers, uptake of maternal and child health services, and health outcomes in western rural China - Huan Zhou; Yuju Wu; Chengfang Liu; Chang Sun; Yaojiang Shi; Linxiu Zhang; Alexis Medina; Scott Rozelle (BMC, 2020)
Abstract Background Empirical evidence suggests that the uptake of maternal and child health (MCH) services is still low in poor rural areas of China. There is concern that this low uptake may detrimentally affect child health outcomes. Previous studies have not yet identified the exact nature of the impact that a conditional cash transfer (CCT) has on the uptake of MCH services and, ultimately, on child health outcomes. The objective of this study is to examine the relationship between CCT, uptake of MCH services, and health outcomes among children in poor rural areas of western China. Methods We designated two different sets of villages and households that were used as comparisons against which outcomes of the treated households could be assessed. In 2014, we conducted a large-scale survey of 1522 households in 75 villages (including 25 treatment and 50 comparison) from nine nationally designated poverty counties in two provinces of China. In each village, 21 households were selected based on their eligibility status for the CCT program. Difference-in-difference analyses were used to assess the impact of CCT on outcomes in terms of both intention-to-treat (ITT) and average-treatment-effects-on-the-treated (ATT). Results Overall, the uptake of MCH services in the sample households were low, especially in terms of postpartum care visits, early breastfeeding, exclusive breastfeeding, and physical examination of the baby. The uptake of the seven types of MCH services in the CCT treatment villages were significantly higher than that in the comparison villages. The results from both the ITT and ATT analyses showed that the CCT program had a positive, although small, impact on the uptake of MCH services and the knowledge of mothers of MCH health issues. Nonetheless, the CCT program had no noticeable effect on child health outcomes. Conclusions The CCT program generated modest improvements in the uptake of MCH services and mothers' knowledge of MCH services in poor rural areas of Western China. These improvements, however, did not translate into substantial improvements in child health outcomes for two potential reasons: poor CCT implementation and the low quality of rural health facilities.